16S rRNA-based detection of oral pathogens in coronary atherosclerotic plaque - Mahendra Jaideep; Mahendra Little; Kurian V; Jaishankar K; Mythilli R (Indian Journal of Dental Research, 2010)
Background: Atherosclerosis develops as a response of the vessel wall to injury. Chronic bacterial infections have been associated with an increased risk for atherosclerosis and coronary artery disease. The ability of oral pathogens to colonize in coronary atheromatous plaque is well known. Aim: The aim of this study was to detect the presence of Treponema denticola, Porphyromonas gingivalis and Campylobacter rectus in the subgingival and atherosclerotic plaques of patients with coronary artery disease. Materials and Methods: Fifty-one patients in the age group of 40-80 years with coronary artery disease were selected for the study. DNA was extracted from the plaque samples. The specific primers for T. denticola, C. rectus and P. gingivalis were used to amplify a part of the 16S rRNA gene by polymerase chain reaction. Statistical Analysis Used: Chi-square analysis, correlation coefficient and prevalence percentage of the microorganisms were carried out for the analysis. Results: Of the 51 patients, T. denticola, C. rectus and P. gingivalis were detected in 49.01%, 21.51% and 45.10% of the atherosclerotic plaque samples. Conclusions: Our study revealed the presence of bacterial DNA of the oral pathogenic microorganisms in coronary atherosclerotic plaques. The presence of the bacterial DNA in the coronary atherosclerotic plaques in significant proportion may suggest the possible relationship between periodontal bacterial infection and genesis of coronary atherosclerosis.